2017
DOI: 10.1016/j.rmed.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dysfunctional breathing on the assessment of asthma control

Abstract: Dysfunctional breathing is common among asthma patients in a specialist setting, and results in a clinically significant underestimation of asthma control, which may potentially lead to overtreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 22 publications
6
33
0
4
Order By: Relevance
“…2,3 The best available data suggests that BPD is a common problem, particularly in primary care, where it is estimated to affect at least one in ten individuals. 4 It is also a prevalent co-morbid condition in airways disease 5 and evident in up to half of individuals with severe asthma. 6 The detection of BPD is important, given the beneficial impact of targeted physiotherapy intervention for both symptoms and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The best available data suggests that BPD is a common problem, particularly in primary care, where it is estimated to affect at least one in ten individuals. 4 It is also a prevalent co-morbid condition in airways disease 5 and evident in up to half of individuals with severe asthma. 6 The detection of BPD is important, given the beneficial impact of targeted physiotherapy intervention for both symptoms and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, however, evaluation of this problem has been confounded by a diagnostic approach dependent on questionnaire‐based tools, for example, an NQ score ≥23. Accordingly, there has been concern that the heightened prevalence of DB observed may have arisen as a consequence of an overlap in symptoms between asthma and DB, thus providing poor discrimination . In this study, utilizing both a questionnaire‐based approach and direct specialist physiotherapy assessment, we still detected a high prevalence of DB/BPD.…”
Section: Discussionmentioning
confidence: 70%
“…The presence of DB in asthma is known to have a detrimental impact on quality of life and can confound accurate assessment of asthma control by amplifying symptomatology . At the same time, targeted physiotherapy intervention for DB has been shown to improve asthma‐related quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…by treatment step of treatment). More recently, Veidal et al [23] reported a prevalence of DB of 24% in those with objectively confirmed asthma (i.e. using bronchodilator or bronchoprovocation testing) and found an independent influence of DB on asthma control, even when adjusted for lung function, airway hyperreactivity, demographics, and medication use.…”
mentioning
confidence: 99%
“…Moreover, questionnaires (e.g. Pittsburgh VCD Index [25] or the Nijmegen questionnaire [26]) can act to highlight the presence of ILO and/or DB [14,23], and in some cases provocation laryngoscopy (e.g. during exercise) may be needed.…”
mentioning
confidence: 99%